The moderating role of intellectual capital on the relationship between corporate governance, enterprise risk management and firm performance in Pakistan - Khan, Sajjad Nawaz (2019)
The effect of corporate governance and enterprise risk management on firm performance has remained an issue of concern for researchers and policymakers, owing to the prevalence of global economic crisis, specifically in developing countries. Therefore, the objective of the current study was to examine the relationship between the corporate governance, enterprise risk management, and the performance of the Pakistani firms. In the current study, corporate governance includes board attributes (independent directors, board size, board financial expertise, CEO duality, and gender diversity) and audit committee (size, independence, and number of meeting). Besides, this study aimed to examine the moderating role of intellectual capital between the corporate governance, enterprise risk management and firm performance to bridge the gap in the existing literature. The theoretical foundation of the current study was based on the agency and resource-based view theory. For this purpose, the data was collected from 130 non-financial firms listed in Pakistan Stock Exchange for the period of 2012-2015.The present study utilized regression with correlated Panels Corrected Standard Errors (PCSEs) technique to achieve the research objectives. The findings revealed that the board size, board financial expertise, CEO duality, gender diversity, audit committee size, audit committee independence, and enterprise risk management have significant relationship with firm performance. However, the direct effect of independent directors and audit committee meeting on firm performance is not significant. Meanwhile, the findings also showed that intellectual capital moderates the relationship of board size, CEO duality, gender diversity, audit committee independence, audit committee meeting and enterprise risk management on firm performance. However, the intellectual capitals do not moderate the relationship between independent directors, board financial expertise, and audit committee size with firm performance. Based on the empirical results, the current study also suggested that Pakistani firms should focus on intellectual capital to increase their performance.